Formation of two glass phases in binary Cu-Ag liquid. (15th August 2020) - An, Qi; Johnson, William L.; Samwer, Konrad; Corona, Sydney L.; Goddard, William A.
Abstract: The glass transition is alternatively described as either a dynamic transition in which there is a dramatic slowing down of the kinetics, or as a thermodynamic phase transition. To examine the physical origin of the glass transition in fragile Cu-Ag liquids, we employed molecular dynamics (MD) simulations on systems in the range of 32, 000 to 2, 048, 000 atoms. Surprisingly, we identified a 1st order freezing transition from liquid (L) to metastable heterogenous solid-like phase, denoted as the G-glass, when a supercooled liquid evolves isothermally below its melting temperature at deep undercooling. In contrast, a more homogenous liquid-like glass, denoted as the l -glass, is achieved when the liquid is quenched continuously to room temperature with a fast cooling rate of ~10 11  K/ sec . We report a thermodynamic description of the l -G transition and characterize the correlation length of the heterogenous structure in the G-glass. The shear modulus of the G-glass is significantly higher than the l -glass, suggesting that the first order l -G transition is linked fundamentally to long-range elasticity involving elementary configurational excitations in the G-glass. Graphical abstract: Image, graphical abstract